Can information imprecision be valuable? The case of credit ratings - Biswas, Sonny; Koufopoulos, Kostas; Thakor, Anjan V. (Journal of Financial Intermediation, 2024)
We develop a model in which credit ratings are endogenously coarse relative to the underlying default probabilities, and ratings precision is countercyclical. Ratings coarseness arises from the profit-maximizing behavior of rating agencies, and coarseness may maximize welfare even when greater ratings precision is costlessly available. Because the private outcome may differ from the socially desirable outcome, a social planner can improve welfare by putting a ceiling (floor) on the rating agency’s fee if the desired outcome is coarseness (precision). Strikingly, when information production is costless, ratings coarseness is socially optimal, but it does not arise in the laissez-faire equilibrium, thus inviting regulatory intervention.